Rounsevelle and Edwin Wildman papers - Wildman, Rounsevelle, 1864-1901.; Wildman, Edwin, 1867-1932.
Correspondence, writings, legal papers, subject files, printed matter, and miscellany. Papers of Rounsevelle Wildman relate principally to his service as U.S. consul general at Hong Kong and to events surrounding the Philippine Insurrection, including material relating to Emilio Aguinaldo. Papers of Edwin Wildman deal mainly with the Boxer Rebellion and Leonard Wood's 1920 Presidential campaign. Correspondents include Thomas W. Cridler, George Dewey, John Goodnow, Mark Hanna, John Hay, David J. Hill, John Addison Porter, and Leonard Wood.
Rounsevelle Wildman, diplomat and editor; and Edwin Wildman (1867-1932), diplomat, editor, and war correspondent.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Diplomatic and consular service, American -- Hong Kong; Philippines -- History -- Philippine American War, 1899-1902.; China -- History -- Boxer Rebellion, 1899-1901.; Elections -- United States -- 1920.; Wood, Leonard, -- 1860-1927.; Cridler, Thomas W. -- 1850-1914.; Dewey, George, -- 1837-1917.; Goodnow, John, -- 1858-1907.; Hanna, Marcus Alonzo, -- 1837-1904.; Hay, John, -- 1838-1905.; Hill, David Jayne, -- 1850-1932.; Porter, John Addison, -- 1856-1900.; Aguinaldo, Emilio, -- 1869-1964.; Diplomats; Editors